Behavioral Therapy in Post Menopause Patients with Urine Incontinence Problems – Systematic Review - Lenny Nurhandayani; Renny Endang Kafiar; Johan Berwulo (Jurnal Syntax Admiration, 2024)
A journal search was carried out used the keywords "Postmenopausal women AND Cognitive Behavioral therapy AND urinary incontinence AND meta analysis" to collect relevant articles published in the last 10 years from five databases (ProQuest, PubMed, Science Direct, Ebsco and Google Scholar. Criteria inclusions were: nurses, patients, urinary incontinence, intervention, full text articles, studies that focused on nursing assessment, and written in English. Six journal articles were selected and analyzed using PICO. Results, Non-pharmacological therapy with a behavioral therapy approach with the application of MBSR (Mindfulness based stress reduction) and HEP (Health Enhancement program) as well as Yoga Therapy & PFMT (Pelvic Floor Muscle Training) exercises combined with light physical exercise such as walking, cycling, swimming. for 30 minutes as well as diet modifications can help postmenopausal patients with urinary incontinence. Conclusion: The application of MBSR (Mindfulness based stress reduction) and HEP (Health Enhancement program) as well as Yoga Therapy & PFMT (Pelvic Floor Muscle Training) exercises combined with light physical exercise such as walking, cycling, swimming for 30 minutes and diet modification can reduces the number of episodes of urine leakage and improves all types of urinary incontinence problems as well as quality of life and can be beneficial for sexual function in post menopausal women.